The Dialectics of Lived Moderation in an NU Madrasah Aliyah: Aswaja An-Nahdliyah Education, Ritual Practice, and Student Organization - Muhammad Nurul Mubin; Ahmad Syafii; Sihono Sihono; Ahmad Dwi Nur Khalim; Muhammad Taufiqurrahman (Nazhruna: Jurnal Pendidikan Islam, 2026)
Religious moderation is widely promoted in Indonesia to counter online-fuelled radical and intolerant narratives, yet its enactment at the school level often remains policy-driven and pedagogically thin. This study examines how moderation is internalized in an NU-affiliated Madrasah Aliyah in Jepara through Aswaja An-Nahdliyah lessons, collective rituals, and student organizations. Based on a qualitative case-study design, data were collected through classroom and school-activity observations, semi-structured interviews with seven informants (school leaders, an Aswaja teacher, and students), and document analysis of syllabi, lesson plans, textbooks, and internal policies (November 2023 to January 2024). The findings show that internalization progresses through intertwined stages of knowing, feeling, and doing that correspond to national commitment, tolerance, anti-violence, and cultural accommodation. However, the process remains uneven due to delayed learning resources, lecture-dominated instruction, and inconsistent family reinforcement. Sustaining moderation, therefore, requires an integrated ecosystem that links dialogical pedagogy, ritual participation, and community collaboration so that moderation becomes a lived civic-religious habit rather than a slogan.